Entrepreneurs in diplomacy: Maratha expansion in the age of the vakil - O'Hanlon, R (SAGE Publications, 2020)
In eighteenth century South Asia, ‘political’ vakils are familiar to us principally as diplomats, active in the inter-state negotiations of the period. They were unlike their predecessors, the īlchī and hejib of earlier centuries, who were associated with the service of courts and states. Maratha political vakils, like others, worked rather more as the mobile agents of individual rulers. Their activities extended far beyond the diplomatic arena. Since revenue rights were central to many inter-state negotiations, vakils often oversaw arrangements for local-level revenue collection. Frequently acting on behalf of several employers, they also had key roles in the remittance of cash, to meet the costs of their own establishments, to participate in the gift economy of the court, to pay the costs of local mercenaries, and to make down-payments for revenue farms on behalf of their employers. Drawing on support of their own extended families, for whom vakil service was often a profession that extended over several generations and regions, many political vakils combined mobility with deep connections to local economies and societies, sharing some characteristics of the ‘portfolio capitalism’ of the eighteenth century. What distinguished them, though, was their access to subcontinent-wide networks of political intelligence, and their expertise in the ‘soft skills’ of negotiation and persuasion, which further enabled them to exploit local social networks and political institutions. Colonial reforms of the late eighteenth century broke this flexible and entrepreneurial service role apart, dissipating it within the lower levels of colonial bureaucracy. The old figure of the political vakil disappeared, to be replaced by the semi-professional ‘native pleader’ in courts of law, and by ‘munshi’ assistants and translators to the Residents of the princely states within the uncovenanted civil service.